Strategi Pengembangan UMKM Dimsum dan Es Teh Pandu Melalui Optimalisasi Pemasaran Digital dan Bauran Pemasaran (4P) - Akhtar Faiz Rabbanie; Aulia Rahma Wahyudi; Axton Axton; Melisha Oktaviana Aisyah; Nila Amalia Nabila; Rika Nabila Azzahra; Zelig Kenzie Kent; Santi Rimadias (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2025)
Increasingly fierce competition and changes in consumer behavior are challenges for Dimsum and Es Teh Pandu MSMEs to continue to grow. This community service aims to overcome these challenges by formulating a strategy for the development of Dimsum and Es Teh Pandu MSMEs through optimizing digital marketing and marketing mix (4P). Through an in-depth analysis of the internal and external factors of MSMEs, including the identification of SWOT and consumer preferences, this community service will identify the most effective marketing strategies. The strategies to be developed include optimizing the use of social media, SEO, content marketing, and optimizing the marketing mix (4P). Thus, it is hoped that Dimsum and Es Teh Pandu MSMEs can increase competitiveness and achieve sustainable growth.